Antibacterial and hemostatic hydrogel via nanocomposite from cellulose nanofibers. (1st September 2018) - Liu, Rui; Dai, Lin; Si, Chuanling; Zeng, Zhaogang
Graphical abstract: Highlights: The CNF/G/Ag0.5 hydrogel has stronger mechanical and self-recovery property. The CNF/G/Ag0.5 hydrogel has satisfactory antibacterial and hemostatic performance. The CNF/G/Ag0.5 hydrogel showed good biocompatibility and wound healing efficacy. Abstract: Bacterial infection and uncontrolled bleeding are the major challenges facing the wound treatment. In order to solve these problems, we have devised a green nanocomposite hydrogel by introducing the aminated silver nanoparticles (Ag-NH2 NPs) and gelatin (G) to carboxylated cellulose nanofibers (CNF). Interpenetrating polymeric network (IPN) was formed by interaction of multicomponent, leading to the non-covalent (dynamic ionic bridges) crosslinked hydrogel CNF/G/Ag. The produced hydrogel dressing with 0.5 mg/mL Ag-NH2 NPs (CNF/G/Ag0.5 ) demonstrated stronger mechanical, self-recovery, antibacterial properties, satisfactory hemostatic performance, and appropriate balance of fluids on the wound bed (2093.9 g/m 2 per day). More importantly, the wound healing model evaluation in vitro and in vivo of CNF/G/Ag0.5 showed an outstanding biocompatibility (∼100% infected cell viability) and wound healing efficacy (∼90% healed and 83.3% survival after 14 days). Our study paved a highly promising approach to improve the performance of cellulose-based hydrogel dressing and would also be useful for developing ideal skin wound dressings by other green materials.